The Transformative Impact of AI on Modern Product Management - Srinivas Sriram Mantrala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of artificial intelligence into product management represents a fundamental shift in how organizations develop, market, and maintain digital products. This comprehensive article explores how AI technologies are transforming product management across multiple dimensions. It examines AI's capacity to revolutionize decision-making through enhanced data intelligence, enabling product teams to uncover insights from vast datasets that would remain hidden to human analysis alone. The article investigates how AI facilitates unprecedented personalization at scale, allowing for tailored user experiences that significantly improve engagement and retention. It further explores predictive analytics capabilities that shift product development from reactive to proactive approaches, forecasting user needs before they are explicitly articulated. Through examination of specific applications like A/B testing enhancement, feature prioritization, churn prediction, and market intelligence, the article demonstrates AI's practical impact on product management workflows. Finally, the article addresses the emerging revolution of generative AI technologies that are creating new possibilities for rapid prototyping, content creation, stakeholder communication, and innovative problem-solving in product development.
Keywords: Artificial Intelligence; Product Development; Personalization; Predictive Analytics; Generative AI